News Strait Times, 30 January 2008 (The New Straits Times Press (M) Bhd, 2008)
"We always have the perception that the private sector has more capable people. The civil servants are sometimes better...their willingness to accept changes and ideas are astounding"-Tan Sri G. Gnanalingham